2002
DOI: 10.1007/s102280200018
|View full text |Cite
|
Sign up to set email alerts
|

Channa nox , a new channid fish lacking a pelvic fin from Guangxi, China

Abstract: A new species of channid fish, genus Channa, is described from 7 specimens collected from the vicinity of Hepu, Guangxi Province, southern China. The new species, Channa nox, is distinguished from all other channid species by the following combination of characters: absence of pelvic fins, small rounded head (22.1%-26.8% SL), narrow interorbital width (19.6%-26.7% HL), short snout length (3.6%-5.1% SL), predorsal and prepectoral lengths (26.9%-28.4% SL and 24.8%-28.3% SL, respectively), 47-51 dorsal fin rays, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
2
7
1
Order By: Relevance
“…Recent taxonomic studies have discovered several new channid species and found unique morphological characters that are common among some species (e.g., Musikasinthorn, 1998Musikasinthorn, , 2000Musikasinthorn and Taki, 2001;Zhang et al, 2002). However, to the best of our knowledge, phylogenetic relationships among the channid species have been rarely studied, whether morphologically or molecularly.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…Recent taxonomic studies have discovered several new channid species and found unique morphological characters that are common among some species (e.g., Musikasinthorn, 1998Musikasinthorn, , 2000Musikasinthorn and Taki, 2001;Zhang et al, 2002). However, to the best of our knowledge, phylogenetic relationships among the channid species have been rarely studied, whether morphologically or molecularly.…”
mentioning
confidence: 96%
“…1), which are characterized by peculiar morphological features, such as an elongated cylindrical body, long and entirely soft-rayed dorsal and anal fins, a large mouth with well-developed teeth on both upper and lower jaws, and an accessory air-breathing apparatus known as the suprabranchial organ (Musikasinthorn, 1998(Musikasinthorn, , 2003. In addition, some Asian species entirely lack pelvic fins (Zhang et al, 2002;Musikasinthorn, 2003). Snakeheads are important food fishes in many countries within their distributional range, and some colorful species are even common in the aquarium trade (Ng and Lim, 1990;Musikasinthorn, 2003;Courtenay and Williams, 2004).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Their significance as food fishes lead to an early burst of species discovery and thus the majority of species was described before the start of the 20 th century. The last two decades, however, have seen a renewed interest in snakehead taxonomy and eight new species have since been described (Musikasinthorn 1998(Musikasinthorn , 2000Zhang et al 2001;Britz 2008;Geetakumari & Vishwanath 2011;Nguyen 2011). Material of a dwarf snakehead lacking pelvic fins from West Bengal has recently been brought to my attention.…”
Section: Introductionmentioning
confidence: 99%